Study Sifat Fisis Dan Mekanis Bahan Polipropilena Pada Produk Penutup Spion Sepeda Motor Merk A Dan Merk B - Sriyanto, Sriyanto, Joko Sedyono, ST, M.Eng, Ph.D (2017)
In this thesis, to investigate the physical and mechanical properties of polymer materials in products cover rearview merc A and merc B. This study is divided into several stages. The first phase specimen procurement and manufacture of test specimens. Tests conducted in accordance with ASTM standards. Tensile strength test to ASTM D 638, hardness testing to ASTM D 2240 and the impact test with standard ASTM D 256. To determine the physical properties of the two products is done by testing SEM and EDS. The second stage of data processing, data analysis and discussion of research results. From the results of the research we concluded that the products cover rearview merc B has a tensile strength and higher hardness than products cover rearview merc A while for the impact rearview cover merc A higher than the rearview cover merc B value tensile strength rearview merc B amounted to 23,846 N/mm2, while the value of tensile strength rearview merc A amounted to 18,276 N/mm2 and strain value rearview merc B 13,333%. To view mirror merc A strain value of 14,667%. The test results impact on the mirror merc A of 36,450 J/mm2, while the hardness value of 64,50 Shore Hardness D. For the impact test results rearview merc B values obtained 34,349 J/mm2 and a hardness value of 66,60 Shore Hardness D. From the SEM images and EDS as well as from observations showed that the rearview merc B discount densities nicer than the rearview merc A. Keywords: polymer, physical properties, mechanical properties, rearview.